Non-targeted metabolomics revealing the effects of bisphenol analogues on human liver cancer cells - Jia, Shenglan (2022)
Bisphenol analogues (BPs) are widely used in plastics, food packaging and other commercial products as non safer alternative of BPA. As emerging environmental contaminants, BPs have received considerable attention for their adverse effects on human health. However, their effects on liver metabolisms are only marginally understood. In this study, high-resolution mass spectrometry-based global metabolomics and extracellular flux (XF) analysis were applied to characterize the cellular metabolome alterations and reveal the possible mechanisms of the metabolic disorders associated with BPs-induced toxicity in HepG2 cells. BPE, BPB and BPAP with similar chemical structures were selected to compare their interference with different metabolic pathways. A total of 61 key metabolite profiles were significantly altered after exposure to the three BPs. Overall, BPs altered metabolites which are associated with energy metabolism, oxidative stress, cell proliferation and nucleotides synthesis. The primary dysregulated pathways included energy and nucleotides synthesis related Purine and Glycolysis/Gluconeogenesis metabolism. In addition, attenuated mitochondrial function and enhanced glycolysis were found under BPB and BPAP treatment. While attenuated glycolysis was observed under BPE treatment. These findings may provide potential biomarkers indicating the cytotoxicity of BPs and prompt a deeper understanding of the intramolecular metabolic processes induced by BPs exposure.